The prevalence of credit risk in Greek Banking: Risk management & methodology for evaluating corporate credit risk and Greek Business Environment - Chrysanthi Balomenou; John Magridis (European Regional Science Association (ERSA), 2011)
Our article consists of the following 4 parts: - In the first part: documented the importance of credit risk with the presentation - analysis of the growth of 6 Greek major financial institutions loan portfolio, for the period 2001 to 2008 and comparison of the loan amount with their own funds and total assets them (based on published accounts). - In the second part: we refer to the approval and monitoring procedures that should be followed by banks using the internal ratings (IRB) methods for corporate loans. Our interest is focused on linking credit ratings to the terms of financing (collateral costs) and on the importance of evaluation / assessment and collateral for the balance of exposures. For typesetting the above is estimated the Risk Weight Assets for PD rating scale (National Bank of Greece published data) and relevant Figure/diagram. - In the third part: we analyse the methodology of key criteria for evaluating the creditworthiness of companies. At the same time for a short description of Greek Business environment we used the -List Easy of Doing Business index 2010- of the World Bank and the results of the assessment of business sectors in Greece according to the model of Credit Risk Tracker Greece's Standard & Poor's, as published by the Hellastat. (The key criteria for evaluating creditworthiness of companies mainly come from research on the websites of the companies Fitch, S & P, Moody's KMV, Hellastat, Easy of Doing Business index). - In fourth part: presented, properly treated, the results of empirical research conducted through distribution of questionnaire to 25 experienced in Risk Management, executives, which was called to assess 20 companies on the basis of their specific quantitative and qualitative characteristics. Finally it is noted that in this final part are also presented all the findings and related conclusions, resulting from the scientific research throughout this paper.
Keywords: 330